Evaluating E-Book Effectiveness and the Impact on Student Engagement - Merkle, Adam C.; Ferrell, Linda K.; Ferrell, O. C.; Hair, Joe F. (Journal of marketing education, 2022)
Marketing curricula are experiencing a digital disruption as e-books and other electronic educational resources replace print textbooks. This study investigates student perceptions about the effectiveness of print textbooks and e-books. Specifically, we focus on the perceived effectiveness of e-books and the impact on student engagement. A field-based quasi-experiment was conducted with a sample of 259 students in the Fall semester, and a follow-up sample of 395 students in the Spring semester. The results show a diverse impact of e-books on student engagement. Some aspects of engagement are positively affected while other aspects of student engagement exhibit a neutral or negative leaning impact. The findings also reflect significant variation in e-book effectiveness depending on the course. Finally, we find that e-books moderate the relationship between textbook effectiveness and academic performance engagement. Highly effective e-books result in higher levels of academic performance engagement. Collectively these findings shed light on the current situation and provide a foundation for additional research to further our understanding about e-book effectiveness and its relationship to student engagement.